Teacher Strategies in Developing Nature Based Inclusive Learning to Realize Equitable Education - Amali, M. Rifqi; Dzikrullooh, Rahmania Ramadhani; Romadhona, Azhara; Sari, Ulfi Andrian (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study aims to analyze teachers’ strategies in developing nature-based inclusive learning to realize equitable education at MIS Bilingual Al-Ikhlas Kepanjen, Malang Regency. The research employs a qualitative approach with a descriptive study design. Data were collected through participatory observation, in-depth interviews, and documentation, and were analyzed interactively through the stages of data reduction, presentation, and conclusion drawing. The findings reveal that teachers’ strategies in nature-based inclusive learning consist of three main stages: collaborative planning, adaptive implementation, and personal mentoring. Teachers apply learning by doing, scaffolding, and experiential learning models to foster students’ active participation, empathy, and social responsibility, including for children with special needs (CWSN). The school’s policy support based on the Index for Inclusion framework and the involvement of parents strengthen the implementation of a humanistic and equitable education practice. However, the implementation of these strategies still faces challenges such as limited disability-friendly facilities, curriculum integration, and the readiness of teachers and special education assistants (GPK) in conducting outdoor learning activities. This study recommends the development of teacher training models and community collaboration to support the sustainability of nature-based inclusive learning in elementary schools.